RPS21 Enhances hepatocellular carcinoma development through GPX4 stabilization - Siyuan Wu; Gaochao Wang; Likai Gu; Yinjie Zhang; Zhihuai Wang (Translational Oncology)
The study highlights that RPS21, a gene encoding a component of the 40S ribosomal subunit, plays an oncogenic role in hepatocellular carcinoma (HCC) and may influence tumor aggressiveness by affecting antioxidant capacity. RPS21 was found to be upregulated in HCC through RNA-sequencing of clinical samples and analysis of the TCGA database. Kaplan-Meier survival analyses linked higher RPS21 expression to lower survival rates across multiple metrics (OS, PFS, RFS, DSS). Mutation analysis via the cBioPortal showed that primarily amplifications in RPS21 are associated with a poorer prognosis. Tissue microarrays confirmed higher RPS21 levels in tumor samples, which were associated with more advanced clinical stages and grades. Experimental interventions involving lentiviral knockdown or overexpression of RPS21 significantly altered HCC cell proliferation and migration. These findings were supported by mouse models, which showed impacts on tumor growth and metastasis. Further mechanistic studies indicated that RPS21 modulates the ubiquitination and stability of GPX4, a key player in ferroptosis and oxidative stress regulation in HCC cells. This comprehensive study, which merges bioinformatic analysis with laboratory research, positions RPS21 as a viable target for HCC therapy and opens new pathways for understanding and treating liver cancer.